2005
DOI: 10.1097/01.mlr.0000156861.58905.96
|View full text |Cite
|
Sign up to set email alerts
|

Cultural Competence

Abstract: Cultural competence training shows promise as a strategy for improving the knowledge, attitudes, and skills of health professionals. However, evidence that it improves patient adherence to therapy, health outcomes, and equity of services across racial and ethnic groups is lacking. Future research should focus on these outcomes and should determine which teaching methods and content are most effective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
260
0
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 759 publications
(271 citation statements)
references
References 33 publications
9
260
0
2
Order By: Relevance
“…Currently, many cultural competency efforts revolve around discussions of cultural values and practices rather than training and interventions that actually improve clinical practice (Dogra et al 2007). The literature on promoting cultural competence is heavily weighted towards providing conceptual models and guidelines rather than on rigorous evaluation of the outcomes of cultural competency practices (Chipps et al 2008), and studies that empirically examine the impact of such practices on clients are virtually non-existent (Bhui et al 2007;Beach et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Currently, many cultural competency efforts revolve around discussions of cultural values and practices rather than training and interventions that actually improve clinical practice (Dogra et al 2007). The literature on promoting cultural competence is heavily weighted towards providing conceptual models and guidelines rather than on rigorous evaluation of the outcomes of cultural competency practices (Chipps et al 2008), and studies that empirically examine the impact of such practices on clients are virtually non-existent (Bhui et al 2007;Beach et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Of training sessions that have undergone evaluation, results that show effectiveness have been mixed. However, in spite of these limitations, evaluation data have suggested significant improvements in skills, knowledge, behavior, and attitudes after training (Beach et al, 2005;Kardong-Edgren et al, 2005). Notably, a recent study of a lesbian, gay, bisexual, transgender (LGBT) health curriculum showed a significant change in knowledge and beliefs about LGBT individuals among second-year medical students at the University of California at San Francisco, including an increase in awareness that sexual orientation and gender identity are clinically relevant (Kelley, Chou, Dibble, & Robertson, 2008).…”
mentioning
confidence: 91%
“…115 This contrasts with the more traditional concept of the provision of 'culturally fitting care' that involves matching a person's needs based on an understanding of the clients' culture in terms of caring actions, health-care information and knowledge particular to each culture. 116 Such a 'fact file' approach to assumed cultural characteristics of ethnic groups fails to capture the diverse and fluid nature of culture and ethnicity and may lead to reifying existing racial categories rather than achieving the intention of deconstructing barriers to health care.…”
mentioning
confidence: 99%